More than a farmer's wife voices of American farm women, 1910-1960 - Lauters, Amy Mattson, 1972- (University of Missouri Press, 2009)
"Examining how women were presented in farming and mainstream magazines over fifty years and interviewing more than 180 women who lived on farms, Lauters reveals that, rather than being victims of patriarchy, most farm women were astute businesswomen, working as partners with their husbands and fundamental to the farming industry"--Provided by publisher.